USM-SCSIO SIGNS MoU TO ENHANCE COLLABORATION IN COASTAL AND MARINE RESEARCH AND CONSERVATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 6 April 2015 – Universiti Sains Malaysia (USM) and South China Sea Institute of Oceanology (SCSIO), Chinese Academy of Sciences, from the People's Republic of China today signed a Memorandum of Understanding (MoU) to enhance collaborative efforts in coastal and marine research and conservation.